HUBUNGAN PRE-EKLAMPSIA, PARITAS, USIA KEHAMILAN DENGAN BAYI BERAT LAHIR RENDAH DI RSUD ARIFIN ACHMAD PROVINSI RIAU TAHUN 2019-2021 - Syamsul Bahri Rivai; Ardita Aldama (Collaborative Medical Journal, 2025)
Globally, 15-20% of all births, or over 20 million newborns annually, are low birth weight (LBW) babies. In Indonesia, 2018 data revealed that 6.2% of children under five with birth weight records were born LBW. LBW infants are prone to cognitive deficits, motor delays, cerebral palsy, and other behavioral and psychological issues. Maternal conditions like preeclampsia, parity, and gestational age are significant contributors. Preeclampsia, characterized by placental abnormalities and maternal systemic inflammation, impairs fetal growth. In multiparous women, suboptimal endometrium can reduce nutrient delivery to the fetus, raising the risk of LBW. Additionally, pregnancies that do not reach full term increase the likelihood of LBW due to incomplete fetal development. This research aimed to analyze the relationship between preeclampsia, parity, and gestational age with low birth weight (LBW) insidence. This research was an observational analytic study with a case-control design to determine the relationship between preeclampsia, parity, and gestational age with the incidence of LBW at Arifin Achmad Hospital, Pekanbaru. Univariate data analysis was presented in the form of frequency distribution tables, and bivariate analysis was conducted using the chi-square test. The study found that there is a relationship between preeclampsia and LBW (p-value: 0.002; OR 2.549; CI 95%: 1.424-4.561). There is no relationship between parity and LBW (p-value: 0.229) There is a relationship between gestational age and LBW (p-value: 0.000; OR 25.806; CI 95%: 14.463-46.047)